The experience of dual career through Slovak athletes` eyes - Geraniosova, K.; Ronkainen, N. (Physical Culture and Sport. Studies and Research, 2015)
The purpose of this study was to examine how Slovak athletes experience dual career (the combination of an athletic career with education and/or work). The study strived to gain an understanding of the athletes` attitudes towards education as well as perceived difficulties and supporting elements in pursuing dual career. Five athletes were interviewed once for approx. 105 min. The interviews and data analysis were based on Intepretative Phenomenological Analysis (IPA) and the interviews were focused on their experience in combining an athletic career with education or work. The athletes experienced dual career as manageable as long as they were assisted by at least simple supportive structures and provided flexible arrangements. Peers had played an important role in athletes` decision-making concerning dual career and in providing social support when facing challenges within dual career. The teachers` prejudice against the athletes based on their athletic role and the lack of dual career structures appeared to be significant deficiencies in dual career support. Finally, the analysis revealed the negative perception of athletes and sport science students by educational representatives. This perception may be a hurdle to be overcome in future dual career development.